Natureza e conhecimento nas pesquisas de Aziz Ab Sáber e Eneas Salati - Gnaccarini, Isabel Cristina Silveira (2014)
This dissertation examines the interdisciplinarity field from reading the researches of geographer Aziz Ab Sáber and from phisical and agronomist engeneer Eneas Salati, with the purpose of linking Knowledge and Nature in their researches. The integrative perspective is present in both scientific legacy and seems to be what earned them significant discoveries about South-American Continent. The idea of interdisciplinary science building is essential to the analysis of contemporary thems, such as climate changes and the rapid and severe impacts of environmental degradation on the ecosystems balance and on the society. The knowledge about Nature of the scientisdt-explores who roamed the Americas is recovered in this study due to its importance of the institutionalization process of Modern Science. But also due to its participation on the Brazilian Geography building. This study is based on the ability of the pioneers in proposing universal laws from the observation of Earth s diversity, realizing a precise point of view in this endeavor, which emanates a particular conjunction of multiple knowledges. Interdisciplinary practice is seen as critical for the advancement of science today. But it must be especially required for complex issues which relate Man and Nature, na investigation area of Geography. The ecological understanding of natural ecosystems is the start up for its problematization and not only in scientific spheres